PERBANDINGAN FAKTOR YANG MEMPENGARUHI PRESTASI KERJA ANTARA KABUPATEN LAMA DAN BARU DI PROPINSI RIAU - Jumiati Sasmita (PEKBIS, 2012)
The research analysed the public servants’ work performance in Riau Province, withspecial emphasis on the influence of opportunity and work performance.Subsequently, the study analysed the influence of opportunity on wokers’ motivationand their work performance. There are some 7,176 public servants in both provincesand the purpose of this research a sample of 500 respondents were selectedrandomly. Structural Equation Model we used to examine the relationship betweenthe relevant factors, namely opportunity, motivation and work performance. Theresults also showed that the opportunity has a strong influence towards motivationfor the whole sample of Riau Province. It is interesting to note that the opportunityhas no strong influence on the work performance in both, the old and new provincewhich is due to the subjective career development characteristics. This phenomenonis contradicting with the organizational behaviour theory that emphasizes that goodindividual behaviour is essential to enhance work performance. Finally, the resultsalso found that there is a strong influence of the motivation variable towards workperformance for the whole sample of Riau as well as for the new province.Interestingly, the study showed that in the old province there was no influence of themotivation variable towards work performance since the relationship between thesetwo variables is insignificant. This is attributed to the fact that staff that performedwell were not rewarded or appreciated. However, the weak influence of opportunityvariable on the work performance in the old as well as new provinces of Riau provedthat Robbins theory is not relevant in this case. The empirical findings can be usedas guidelines for the Riau Government towards shaping and improving the existingpolicies and programs aimed at enhancing the public servants’ work performance inthe future, particularly with regards to the personality factors which should receivedserious attention among administrators of the Riau Province.